Toponymic restoration and media text as a marker of urban identity crisis - Gimelshteyn, Alexander; Gimelshtein, Irina (project baikal, 2023)
The modern media text is considered as one of the markers of the urban identity crisis. Since the 1960s there has been an active social movement for the preservation of cultural monuments in Irkutsk. The importance of historical toponyms for the city identity is generally recognized in the professional and cultural sphere. This provided an opportunity to manifest the theme of toponymic restoration. The wave of partial toponymic restoration in historical Russian cities in the 1990s was completely ignored by the Irkutsk authorities, and there were just a few cases of opportunistic renaming of godonyms beyond it. In the contemporary crisis processes, media acts through media texts as identifiers, crisis markers, informants, conflict producers, the space of crisis manifestations and the medium of conflict propagation.
Keywords: crisis; identity; media text; toponymic restoration; discourse; conflict